Effect of PANI on Thermal, Mechanical and Electromagnetic Properties of HDPE/LLDPE/PANI Composites - Patrick Valadão de Faria; Eduardo Henrique Backes; Larissa Stieven Montagna; Simone de Souza Pinto; Luiz Antonio Pessan; Mirabel Cerqueira Rezende; Fabio Roberto Passador (Materials Research, 2017)
In this work, polyaniline (PANI) in emeraldine-base form, synthesized by chemical oxidation polymerization, was protonated with hydrochloric acid (HCl). Composites based on high-density polyethylene (HDPE) and linear-low density polyethylene (LLDPE) blends with PANI were prepared in molten condition using a torque rheometer. The effect of compatibilizer agent (maleic anhydride-grafted high density polyethylene, HDPE-g-MA) and different contents of PANI on the blends-based composites was also investigated. Thermal, mechanical, and electromagnetic (electric permittivity) measurements and morphological aspects of the composites were evaluated. The addition of PANI content in the composites decreases the degree of crystallinity of HDPE and LLDPE blends, which implies that PANI particles make it difficult for co-crystallization to occur in the HDPE and LLDPE, respectively. On the other hand, the addition of compatibilizer agent in the HDPE and LLDPE blends increased the degree of crystallinity. The complex parameters of permittivity in the frequency range of 8.2 to 12.4 GHz varied as a function of the PANI content in the blend. It was also observed that the compatibilizer agent increased the composite stiffness and decreased the electric permittivity values. This result shows that the increasing rigidity of the molecular structure of the polyethylene matrix hindered the dissipation of the electromagnetic energy in the sample.